The Effect of Different Interfaces and Confinement on the Structure of the Ionic Liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide Entrapped in Cationic and Anionic Reverse Micelles. - Ferreyra, Darío David (2012)
The behavior of the ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([bmim][Tf 2N]) entrapped in two reverse micelles (RMs) formed in an aromatic solvent as dispersant pseudophase: [bmim][Tf 2N]/benzyl-n-hexadecyldimethylammonium chloride (BHDC)/chlorobenzene and [bmim][Tf 2N]/sodium 1,4-bis-2- ethylhexylsulfosuccinate (AOT)/chlorobenzene, was investigated using dynamic light scattering (DLS), FT-IR and 1H NMR spectroscopies. DLS results reveal the formation of RMs containing [bmim][Tf 2N] as a polar component since the droplet size values increase as the W s (W s = [[bmim][Tf 2N]]/[surfactant]) increases. Furthermore, it shows that the RMs consist of discrete spherical and non-interacting droplets of [bmim][Tf 2N] stabilized by the surfactants. Important differences in the structure of [bmim][Tf 2N] entrapped inside BHDC RMs, in comparison with the neat IL, are observed from the FT-IR and 1H NMR measurements. The electrostatic interactions between anions and cations from [bmim][Tf 2N] and BHDC determine the solvent structure encapsulated inside the nano-droplets. It seems that the IL structure is disrupted due to the electrostatic interaction between the [Tf 2N] - and the cationic BHDC polar head (BHD +) giving a high ion pair degree between BHD + and [Tf 2N] - at a low IL content. On the other hand, for the AOT RMs there is no evidence of strong IL-surfactant interaction. The electrostatic interaction between the SO 3 - group and the Na + counterion in AOT seems to be stronger than the possible [bmim] +-SO 3 - interaction at the interface. Thus, the structure of [bmim][Tf 2N] encapsulated is not particularly disrupted by the anionic surfactant at all W s studied, in contrast to the BHDC RM results. Nevertheless, there is evidence of confinement in the AOT RMs because the [bmim] +-[Tf 2N] - interaction is stronger than in bulk solution. Thus, the IL is more associated upon confinement. Our results reveal that the [bmim][Tf 2N] structure can be modified in a different manner inside RMs by varying the kind of surfactant used to create the RMs and the IL content (W s). These facts can be very important if these media are used as nanoreactors because unique microenvironments can be easily created by simply changing the RM components and W s.